A use-case driven approach to systematic functional decomposition: a case of the biopsy procedure in breast cancer treatment. (9th March 2007) - Park, Namkyu; Youn, Cheong; Ellis, R. Darin
Functional decomposition is a widely used system modelling technique for understanding complex systems. It is based on functional partitioning of the problem domain and requires identification of a system's functionalities. The identification of a system's functionalities is performed informally by the analyst without any systematic guideline. Approaches which employ this technique have, therefore, difficulty in such identification of functionalities. This paper proposes a use-case driven functional decomposition approach. This approach has two major advantages. Firstly, the identification of a system's functionalities is easier than the classical approaches. Secondly, the system requirements and implementation can be easily validated with the users of the system. It also matches well with common functional decomposition approaches like Structured Analysis as it is also a top-down approach. The approach is presented along with an example of its application. We also provide engineering steps, heuristics and guidelines.